1986
DOI: 10.1172/jci112730
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of lethal murine graft versus host disease by treatment of donor cells with L-leucyl-L-leucine methyl ester.

Abstract: Graft vs. host disease (GVHD) remains one of the main problems associated with bone marrow transplantation. The current studies were undertaken to determine whether treatment of the donor inoculum with the anticytotoxic cell compound L-leucyl-L-leucine methyl ester (Leu-Leu-OMe) would alter the development of GVHD in a murine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 21 publications
(10 reference statements)
2
16
0
Order By: Relevance
“…LeuLeuOMe was initially shown to be extremely effective in killing various immune and myeloid tumor cells of bone-marrow origin and to efficiently protect against graft-versus-host disease in a mouse model of bone marrow transplantation (29,48). Later studies suggested that other cell types are susceptible to the compound but with lower sensitivity (32,49).…”
Section: Leuleuome Triggers Cathepsin-dependent Apoptosis In Eight DImentioning
confidence: 99%
See 1 more Smart Citation
“…LeuLeuOMe was initially shown to be extremely effective in killing various immune and myeloid tumor cells of bone-marrow origin and to efficiently protect against graft-versus-host disease in a mouse model of bone marrow transplantation (29,48). Later studies suggested that other cell types are susceptible to the compound but with lower sensitivity (32,49).…”
Section: Leuleuome Triggers Cathepsin-dependent Apoptosis In Eight DImentioning
confidence: 99%
“…It has been * This work was supported by Ministry of Higher Education, Science, and shown that lysosomes are particularly sensitive toward oxidative stress (21)(22)(23)(24). In addition, LMP can be induced by anticancer agents, such as siramesine, a novel sigma-2 receptor ligand (25), cardenolide (UNBS1450) (26), biphosphinic palladacycle complex (27) and novel compounds that target p53-independent apoptosis (28), by detergents including LeuLeuOMe, which was shown to have a protective effect in a model of graft versus host disease (29) and is currently in phase II clinical trials, and by a number of other stimuli (17, 30 -33).…”
mentioning
confidence: 99%
“…The fact that long-term survival was uniformly observed in these mice despite development of severe transmural intestinal GVHD suggests that other aspects ofGVHD such as the profound immunosuppression reported to be present in B6 -* B6D2F1 GVHD mice but not in DBA/2 --B6D2Fl mice (20-22) or B6D2Fl recipients of Leu-Leu-OMe treated B6 donor cells (31) might be a far more important determinant of overall mortality rates. Indeed, even in the B6 --B6D2Fl strain combination in which recipients of Leu-Leu-OMe-treated donor cells consistently fail to exhibit clinically apparent wasting or diarrhea (17,18,31), histologic evaluation 4 wk after transplantation has also demonstrated extensive colonic inflammatory changes (data not shown). Since the early mortality observed in many strain combinations prevents detailed chronologic evaluation of enteropathic GVHD, the uniformly prolonged survival of B6D2Fl recipients of DBA/2 donor T cells afforded an opportunity to examine in detail the features of intestinal GVHD generated by various donor T cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the salutary effect of LeuLeu-OMe treatment of donor cells on the course of GVHD in B6 -> B6D2Fl mice suggests that cytotoxic lymphocytes play an essential role in the evolution of GVHD in this class I + II MHC antigen and multiple non-MHC antigen disparate strain combination. Furthermore, inasmuch as depletion of CD4(+) T cells, CD8(+) T cells, or NK cells alone does not prevent lethal GVHD in this strain combination (17,18), these findings demonstrated that Leu-Leu-OMe treatment ofdonor cells offers a unique approach to prevention of this complication of bone marrow transplantation.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation